Volume 1: Turbomachinery 1991
DOI: 10.1115/91-gt-127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Rotation on Tip Leakage in a Planar Cascade of Turbine Blades: Part I — Tip Gap Flow

Abstract: The paper presents further results from a continuing study on tip leakage in axial turbines. Rotation has been simulated in a linear cascade test section by using a moving-belt tip wall. Measurements were made inside the tip gap with a three-hole pressure probe for a clearance size of 3.8 percent of the blade chord. Two wall speeds are considered and the results are compared with the case of no rotation. As in other experiments, significant reduction in the gap mass flow rate is observed due to the relative mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 8 publications
(10 reference statements)
2
30
0
Order By: Relevance
“…For a flat tip, the effects of endwall motion reduce the size of the separation zone near the pressure side edge of the blade tip. This was observed by Yaras and Sjolander [9] using three-hole probe measurements inside the tip gap, by Palafox et al [10] using PIV measurement and by Krishnababu et al [11] using numerical methods. Liu et al [13] assessd different turbulence models for the predction of tip leakage vortex.…”
Section: Introductionmentioning
confidence: 69%
“…For a flat tip, the effects of endwall motion reduce the size of the separation zone near the pressure side edge of the blade tip. This was observed by Yaras and Sjolander [9] using three-hole probe measurements inside the tip gap, by Palafox et al [10] using PIV measurement and by Krishnababu et al [11] using numerical methods. Liu et al [13] assessd different turbulence models for the predction of tip leakage vortex.…”
Section: Introductionmentioning
confidence: 69%
“…Low-speed experimental studies using a moving belt were conducted by Yaras and Sjolander [15] showing a substantial reduction of tip gap flow. Tallman and Lakshminarayana [16] used simulations showing the implications of reduced gap flow and its effect on the tip leakage vortex.…”
mentioning
confidence: 99%
“…Viscous effects also play an important role. Yaras and Sjolander (1992) investigated in an extensive experimental work, the physical mechanisms that could reduce the tip leakage flow due to the rotationally-induced relative motion of the end wall. Other results (Yamamoto, 1988) have shown that there is a strong interaction between the tip leakage vortex and the passage vortex.…”
Section: Free-standing Bladesmentioning
confidence: 99%